Physical and mechanical properties of kenaf fiber-nr biocomposite / Nadiyatul Husna Jamhari - Jamhari, Nadiyatul Husna (Faculty of Applied Sciences, 2009)
Kenaf is known as the natural fiber that content highly composition of cellulose and renewable fibers. It is used for industrial products, can also be utilized as a cost effective and environmentally acceptable approach to the creation of a partially biodegradable molded grade biocomposite. These renewable fibers have low densities and high specific properties and their non-abrasive nature permits a high volume of filling in the composite. In this study, compression molding is used to fabricate these biocomposite. The effects of Kenaf as filler in natural rubber was study involved optimizing and studying the composition percentages of the compounds being used. Moreover, the properties of the product by using tensile test, water absorption test, hardness test and density test is observed